A decade in the West : Painting, Sculpture and Graphics from the Anderson Collection. - Santa Barbara Museum of Art, Santa Barbara (Stanford : Stanford University Museum of Art, 1971)
Allen, William ; Arneson, Robert ; Barletta, Joel ; Beall, Dennis ; Beasley, Bruce ; Benton, Fletcher ; Bengston, Billy Al ; Boyle, Keith ; Diebenkorn, Richard ; Francis, Sam ; Grant, James ; Gooch, Gerald ; Gutkin, Peter ; Heck, Howard E. ; Harvey, Robert M. ; Holland, Tom ; etc.
A decade in the West : Painting, Sculpture and Graphics from the Anderson Collection, Stanford University Museum of Art, Stanford, 12 June to 22 august 1971 ; Santa Barbara Museum of Art, Santa Barbara, 10 September to 10 October 1971
boek